Coordinating healthcare and pension policies: An exploratory study - Azad Singh Bali; Mukul G. Asher (Asian Development Bank Institute (ADBI), 2012)
Rapid ageing of the population globally represents an unprecedented historical trend. As pension and healthcare costs are positively correlated with rising incomes, ageing, urbanization, and a shift from communicable to life-style diseases, managing these costs is a major challenge. There are many linkages between healthcare and pension arrangements - in terms of costs, exposure to risks, and as they jointly impact on crucial policy decisions. This paper discusses the rationale for coordination between various programs to better manage the cost of ageing. The current difficult macroeconomic environment, including fiscal stringency conditions, strengthens the case for such coordination.
Keywords: J1; J4; 330; population ageing; pension policies; healthcare policies; urbanization; Alternde Bevölkerung; Gesundheitskosten; Rentenfinanzierung; Soziale Kosten; Sozialpolitik; Internationale Wirtschaftspolitik; Welt